PERANCANGAN ALAT PENGENDALI LISTRIK JARAK JAUH DENGAN ANDROID UNTUK PENGHEMATAN BIAYA LISTRIK - Dian Gustina; Toni Wirawan (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2017)
Microcontroller is a microcomputer and microprocessor technology breakthrough, which has been widely used in electronic circuit applications. By utilizing the functionality of a microcontroller and android application, then the application will be made an electric appliance remote control with android. The purpose of this application to meet the needs of people who have mobility is high enough to offset the price of electricity is high enough. This application uses the android application to allow users to remotely control electricity. Electrical home will be on / off as the user desires. Application of electric remote control makes it easy to control remote history of electricity, especially for people who need mobility is high enough and wants everything very practical.Â Keyword : Microcontroller ATMEGA 16, Electrical, Android.